Salivary inflammatory biomarkers and glycated haemoglobin among patients with type 2 diabetic mellitus - Ekhosuehi Theophilus Agho; Foluso John Owotade; Babatope Ayodeji Kolawole; Elijah Olufemi Oyetola; Tewogbade Adeoye Adedeji (BMC, 2021)
Abstract Background Type 2 diabetes mellitus has reached epidemic proportions worldwide and improved detection techniques and biomarkers are urgently needed across the spectrum of diabetes initiation and progression. Inflammatory biomarkers play a role in the development of the condition and blood is the gold standard body fluid for the diagnosis of diabetes mellitus. Serum glycated haemoglobin is a widely used marker of chronic hyperglycemia, and it is currently used to diagnose type 2 diabetes mellitus and it is the standard biomarker for the adequacy of management. However, saliva offers an alternative to serum as a biological fluid for diagnostic purposes. Non-invasive measures of inflammatory biomarkers (such as saliva diagnostics) are increasingly being investigated due to significant similarities between salivary and serum proteome. The role of saliva diagnostics in diabetes mellitus has not been explored in our study population. Objectives This study investigated the association of selected salivary inflammatory biomarkers (Interleukin 6 [IL-6], C-reactive protein [CRP], and Tumour necrosis factor α [TNF-α]) to glycated haemoglobin (HbA1C) in type 2 diabetics. Materials and methods Seventy-five participants, 39 type 2 diabetics (52%) and 36 (48%) healthy controls were recruited. Saliva and blood samples were collected for each participant. The levels of selected salivary inflammatory biomarkers (IL-6, CRP and TNF-α) were estimated by Enzyme Linked Immunosorbent Assay (ELISA) method and glycated haemogloin (HbA1C) was estimated using the liquid chromatography method. Periodontal status of the participants were determined using the Basic Periodontal Examination (BPE). Results The mean salivary levels of CRP was significantly higher in diabetics, 0.05 ± 0.04 µg/ml than in controls, 0.02 ± 0.02 µg/ml (p < 0.001). Mean TNF-α was also significantly higher in diabetics, 5.39 ± 12.10 pg/ml than in controls, 1.51 ± 3.66 pg/ml (p = 0.036). Mean salivary IL-6 was also higher in diabetics compared with controls (47.20 ± 18.49 versus 41.94 ± 16.88 pg/ml), but the difference was not statistically significant, p = 0.204. In the multivariate analysis adjusting for age and periodontal status, only the mean salivary CRP was significantly higher in diabetics, 0.034 higher than controls (95% CI 0.009, 0.059 and p = 0.01). There was a positive correlation between salivary CRP and HbA1C levels, which was moderate with r-value 0.4929 and p-value < 0.0001. Conclusions Salivary inflammatory biomarkers especially CRP are higher in diabetics compared with controls and CRP is positively correlated with serum HbA1C levels. The biomarkers show potentials as non-invasive alternative method to evaluate glycaemic control in diabetes.